2020
DOI: 10.18699/vj20.676
|View full text |Cite
|
Sign up to set email alerts
|

mRNA technology as one of the promising platforms for the SARS-CoV-2 vaccine development

Abstract: After the genome sequence of SARS-CoV-2 (Severe acute respiratory syndrome-related coronavirus 2) was published and the number of infected people began to increase rapidly, many global companies began to develop a vaccine. Almost all known approaches to vaccine design were applied for this purpose, including inactivated viruses, mRNA and DNA-vaccines, vaccines based on various viral vectors, synthetically generated peptides and recombinant proteins produced in cells of insects and mammals. This review consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(24 reference statements)
0
7
0
2
Order By: Relevance
“…Firstly, mRNA vaccines have the excellent safety. Unlike DNA and viral vaccines, mRNA is a non-infectious nucleic acid substance and once delivered to the cytoplasm, the mRNA is translated immediately [ 61 , 126 ]. Since mRNA vaccines do not enter the nucleus and cannot integrate into the genome, there is no risk of causing genetic mutations in recipients [ 61 , 126 ].…”
Section: Future Prospects and Challenges Of Mrna Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, mRNA vaccines have the excellent safety. Unlike DNA and viral vaccines, mRNA is a non-infectious nucleic acid substance and once delivered to the cytoplasm, the mRNA is translated immediately [ 61 , 126 ]. Since mRNA vaccines do not enter the nucleus and cannot integrate into the genome, there is no risk of causing genetic mutations in recipients [ 61 , 126 ].…”
Section: Future Prospects and Challenges Of Mrna Vaccinesmentioning
confidence: 99%
“…Unlike DNA and viral vaccines, mRNA is a non-infectious nucleic acid substance and once delivered to the cytoplasm, the mRNA is translated immediately [ 61 , 126 ]. Since mRNA vaccines do not enter the nucleus and cannot integrate into the genome, there is no risk of causing genetic mutations in recipients [ 61 , 126 ]. Like native mRNAs, the activity of in vitro transcribed mRNAs is transient, and they are fully degraded by physiological metabolic pathways [ 61 ].…”
Section: Future Prospects and Challenges Of Mrna Vaccinesmentioning
confidence: 99%
“…Существуют разные подхо-ды, направленные на разработку универсальной вакцины от гриппа. К ним относится, например, создание рекомбинантных белков-иммуногенов, использование консервативных фрагментов белков вируса гриппа (стебель гемагглютинина, белки NP, PB1, М1 и M2) или разработка новых типов вакцин на основе мРНК [2,3,4,5,7,8,9].…”
Section: Introductionunclassified
“…Помимо ДНК-вакцин, в последние 3-4 года активно развивается другой вид вакцин на основе нуклеиновых кислот, основанных на мРНК [3,4,10]. Данный тип вакцин обладает существенным преимуществом перед другими типами вакцин, в том числе и ДНК-вакцинами.…”
Section: Introductionunclassified
“…Many studies [ 18 , 19 ] have demonstrated that mRNA-based vaccines are a promising platform with such useful features as flexibility, scalability, cheap production, and independence from the cold chain [ 15 ]. Due to the possibility of making a simple change to the target gene in an mRNA vaccine without modifying production technology, one can quickly respond to the emergence of new pandemic infectious agents, especially the influenza virus.…”
Section: Introductionmentioning
confidence: 99%